Microleakage of newly developed glass carbomer cement in primary teeth - Cehreli, Sevi Burcak (Dental Investigations Society, 2013)
OBJECTIVE: Glass carbomer cement represents a new generation of dental material, which mineralizes gradually into fluorapatite. The aim of this study was to evaluate the microleakage and marginal integrity of newly developed glass carbomer cement with and without protective surface coating (SC) in primary molars. METHODS: Standardized cavities were prepared on extracted human primary molars, and the teeth were randomly assigned into the following groups (n = 10/each): (1) conventional glass ionomer cement (GIC) without SC; (2) GIC with SC; (3) glass carbomer cement without SC; (4) glass carbomer cement with SC; and (5) compomer without SC. Following thermocycling (5 ± 2°C–55 ± 2°C, dwell time 15 s, 2000×), the specimens were immersed in 0.5% basic fuchsin solution, sectioned, and digitally photographed. Microleakage was evaluated quantitatively by using open-source image analysis toolkit (ImageJ), and the data were analyzed statistically by using Kruskal-Wallis and Conover’s Multiple Comparison tests (P=.05). RESULTS: The greatest amount of dye leakage was observed in the uncoated glass carbomer specimens, followed by the uncoated glass ionomer group (P<.05). There was no significant difference between the microleakage values of coated glass ionomer, coated glass carbomer, and the compomer (P>.05). The following statistical ranking was observed among microleakage of the test materials: uncoated glass carbomer > uncoated glass ionomer > coated glass ionomer ≈ coated glass carbomer ≈ compomer. Uncoated glass carbomer exhibited severe internal ice crack-like lines. CONCLUSION: The use of the new glass carbomer cement without SC results in severe microleakage and catastrophic internal cracks.